Математичне моделювання перехідних процесів в тяговій установці з синхронним двигуном на постійних магнітах за наявності пускових обмоток - Савеленко, І. В.; Savelenko, Іvan (КНТУ, 2016)
На основі розгляду рівнянь Парка-Горева та застосуванням спостерігача Люенбергера для системи автоматичного керування тяговою установкою, розраховано координати синхронного двигуна з постійними магнітами в перехідних процесах. Доведено переваги використання СДПМ з пусковими обмотками в порівнянні з СДПМ без них. The development of a mathematical model of synchronous motor with permanent magnets in the presence of starting windings to calculate of controlling influences in the regulators ACS of traction drive. Based on consideration of equations Park-Gorev and use of observer Luenberger for automatic control system traction drive, calculated coordinates of the synchronous motor with permanent magnets in the transition process. Proven advantages of SDPM with windings of starts compared to SDPM without them. The use of observer Luenberger allowed to assess the value of starting current model ACS traction system based on SDPM of starting windings that can not be directly measured. Analysis of the effect from the application of the proposed ACS showed that the length of the transition process in the case of SDPM with launchers windings appeared at 7.63% compared with the model of ACS SDPM without launchers windings.
Mathematical modeling of transients in traction drive with synchronous motor on the permanent magnets with of starting winding
Keywords: синхронний двигун на постійних магнітах; спостерігач зниженого порядку; пускові обмотки; перехідний режим; automatic control systems; electric drive; synchronous permanent magnet motor